Preparation method of sodium-promoted zinc-aluminum spinel supported iron-based catalyst and application of catalyst in olefin synthesis

By preparing sodium to promote zinc-aluminum spinel-supported iron-based catalysts and optimizing the carbon dioxide hydrogenation reaction conditions, the shortcomings of the existing catalysts in CO2 conversion are solved, and efficient olefin production effect and catalytic stability are achieved.

CN119701920AActive Publication Date: 2025-03-28CHANGZHOU UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411758333.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-28
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing catalysts for producing low-carbon olefins from carbon dioxide hydrogenation are poor in CO2 conversion and lack zinc-aluminum spinel catalysts for producing olefins.

Method used

A sodium-promoting zinc-aluminum spinel-supported iron-based catalyst was prepared, and iron and sodium elements were loaded onto zinc-aluminum spinel oxides by physical mixing method, and calcined at 550°C to 600°C for 2 to 5 hours to form a catalyst. This catalyst is used in carbon dioxide hydrogenation reaction, with the optimized reaction conditions being temperature 360°C, pressure 2.5MPa, and space velocity 2600ml/(g*h).

Benefits of technology

The catalyst exhibits excellent catalytic performance in carbon dioxide hydrogenation reaction, especially in terms of CO2 conversion, which is higher than 20% of the prior art. It also has good reaction catalytic stability and has the potential for industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005166922620000061
    Figure BDA0005166922620000061
  • Figure HDA0005166922630000011
    Figure HDA0005166922630000011
  • Figure HDA0005166922630000012
    Figure HDA0005166922630000012
Patent Text Reader

Abstract

The invention belongs to the technical field of carbon dioxide hydrogenation catalysts, and discloses a preparation method of a sodium-promoted zinc-aluminum spinel supported iron-based catalyst and application of the sodium-promoted zinc-aluminum spinel supported iron-based catalyst in olefin synthesis. The catalyst comprises a zinc-aluminum spinel oxide carrier prepared from a zinc salt and an aluminum salt according to a molar ratio of 1: 2, a zinc-aluminum spinel oxide, an iron salt and a sodium salt are mixed and uniformly mixed in a physical mixing manner, and then the mixture is calcined at 550-600 DEG C for 2-5 h to obtain the sodium-promoted zinc-aluminum spinel supported iron-based catalyst which is used in a carbon dioxide hydrogenation reaction, and the catalyst has the advantages of simple preparation process and low cost. The optimal catalytic reaction condition is selected by adjusting different reaction conditions, such as reaction temperature, air speed and the like. In addition, the prepared catalyst shows good olefin selectivity and high thermal stability in a carbon dioxide hydrogenation reaction process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a sodium-promoted zinc-aluminum spinel-supported iron-based catalyst. Background Art

[0002] The lack of fossil energy and the problem of carbon emissions have seriously affected human development. The need to develop sustainable clean energy technology has promoted the research on the utilization of CO2. Light olefins are important precursors for the manufacture of plastics, solvents, paints, etc. Carbon dioxide hydrogenation can effectively solve the above problems and produce light olefins. The entire carbon dioxide hydrogenation process needs to go through the reverse water gas reaction (RWGS) and Fischer-Tropsch synthesis (FTS). Fe3O4 and Fe5C2 in iron-based catalysts are the active phases of the above two steps, respectively. Therefore, iron-based catalysts are widely used in the production of olefins by hydrogenation of carbon dioxide. The spinel structure is a special crystal structure with a highly ordered arrangement. The crystal structure of the spinel catalyst is octahedral, with high stability and activity. This structure gives the spinel catalyst a large surface area and good catalytic performance. In the hydrogenation of carbon dioxide, spinel-structured nanocatalysts have many advantages in accelerating the breakage of CO2 bonds and enhancing catalytic performance through the formation and stabilization of active sites.

[0003] At present, there are patent applications for catalysts for the hydrogenation of carbon dioxide to produce low-carbon olefins, but there are no patents using zinc aluminum spinel as a catalyst and used for the hydrogenation of carbon dioxide to produce low-carbon olefins, while there are patents for the production of aromatics. The following is a detailed description of a patent reported on the use of zinc aluminum spinel catalysts for the hydrogenation of carbon dioxide to produce aromatics: Chinese patent CN110496639A is publicly named: A catalyst for the synthesis of aromatics, its preparation method and application. The patent reports a zinc aluminum spinel oxide and an acidic molecular sieve catalyst for the hydrogenation of carbon dioxide to synthesize aromatics. The results show that all catalysts have a relatively high selectivity for aromatics, but the conversion rate of CO2 is not good, generally around 10%. Summary of the invention

[0004] In order to solve the problems in the background technology, the present invention prepares a sodium-promoted zinc-aluminum spinel-loaded iron-based catalyst, which shows good catalytic performance for carbon dioxide hydrogenation to olefins, especially in terms of CO2 conversion rate, and also shows good stability. Therefore, it is expected to scale up experiments and realize industrial application.

[0005] Therefore, an object of the present invention is to provide a catalyst for olefin synthesis, which comprises a zinc aluminum spinel carrier in a molar ratio of 1:2, iron as an active phase on the surface and sodium as a promoter.

[0006] Another object of the present invention is to provide a method for preparing the above catalyst.

[0007] Another object of the present invention is to provide a method for preparing olefins by hydrogenating carbon dioxide using the above catalyst, and to explore the optimal reaction conditions.

[0008] The specific preparation method is as follows:

[0009] Zinc-aluminum spinel: zinc salt and aluminum salt are prepared into a mixed metal salt aqueous solution; the mixed metal salt aqueous solution is contacted with a precipitant aqueous solution until a fixed pH value of 10 is reached, so that the metal ions in the mixed metal salt aqueous solution are co-precipitated; stirring until complete precipitation; washing, drying and calcining the precipitate to obtain the zinc-aluminum spinel oxide;

[0010] Furthermore, the zinc salt is selected from one or more of zinc acetate, zinc sulfate and zinc nitrate; the aluminum salt is selected from one or more of aluminum acetate, aluminum sulfate, aluminum nitrate and aluminum isopropoxide.

[0011] The precipitant is selected from one or more of sodium carbonate, potassium carbonate, ammonium carbonate, sodium bicarbonate, potassium bicarbonate, ammonium bicarbonate, ammonia water, sodium hydroxide, and potassium hydroxide;

[0012] Further, the zinc-aluminum spinel carrier is prepared in a molar ratio of zinc salt to aluminum salt of 1:2;

[0013] The coprecipitation is carried out at 40°C to 80°C; and the carrier calcination is carried out at 600°C to 900°C.

[0014] Sodium-promoted zinc-aluminum spinel-loaded iron-based catalyst: the iron and sodium elements are loaded by a physical mixing method and then calcined.

[0015] Sodium-promoted zinc-aluminum spinel-supported iron-based catalyst: zinc-aluminum spinel oxide, iron salt and sodium salt are mixed, uniformly mixed by physical mixing, and then calcined at 550° C. to 600° C. for 2 to 5 hours to obtain.

[0016] Furthermore, the mass ratio of the iron salt to the zinc-aluminum spinel carrier is 1:1-1.5, and the molar ratio of iron to sodium is 7:1.5-1.8.

[0017] The invention provides an application of a sodium-promoted zinc-aluminum spinel-supported iron-based catalyst material in chemical catalysis, specifically, an application in obtaining high-value chemicals, especially olefins, through the use of carbon dioxide and hydrogen at high temperature and high pressure.

[0018] It is used as a catalyst in the carbon dioxide hydrogenation reaction. The catalyst is loaded into a catalytic reactor, pre-treated with hydrogen reduction for 18 hours, and then switched to a mixture of H2 and CO2 in a ratio of 2:1 to 4:1, and hydrogenated to olefins at a temperature of 280 to 380°C, a pressure of 2.4 to 2.6 MPa, and an air velocity of 1400 to 3000 ml / (g*h), and the reaction time is 75 hours.

[0019] The sodium-promoted zinc-aluminum spinel-supported iron-based catalyst provided by the present invention is used for the carbon dioxide hydrogenation reaction under the above reaction conditions, and finally compared to select the best reaction conditions. The best reaction conditions are: reaction temperature of 360°C, reaction pressure of 2.5MPa, and space velocity of 2600ml / (g*h).

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: the zinc aluminum spinel carrier in the catalyst of the present invention is simple to prepare and has low raw material cost. The present invention uses it for the first time in the hydrogenation of carbon dioxide to olefins, with iron as the active phase on the surface and sodium as the auxiliary agent. The obtained reaction shows excellent catalytic performance, especially in terms of CO2 conversion rate, and also shows good reaction catalytic stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 XRD diagrams of the catalyst supports of Examples 1-10 and Comparative Examples 1-4;

[0022] Figure 2 XRD diagrams of Examples 1-10 and Comparative Examples 1-4 after catalyst loading;

[0023] Figure 3 This is a graph showing the change in CO2 conversion rate over time in the catalytic reaction of the catalysts in Example 9 and Comparative Examples 1-4. DETAILED DESCRIPTION

[0024] Example 1

[0025] Zinc-aluminum spinel: 3.86g Zn(NO3)2·6H2O, 9.75g Al(NO3)3·9H2O and 150ml deionized water are prepared into a mixed metal salt aqueous solution; 5.6g NaOH is dissolved in 100ml deionized water to form a precipitant solution, and the precipitant aqueous solution is dripped into the metal salt aqueous solution, and the precipitation reaction temperature is controlled at 60°C until a fixed pH value of 10 is reached, so that the metal ions in the mixed metal salt aqueous solution are co-precipitated; stirring until complete precipitation; washing the precipitate with deionized water 5 times, drying at 70°C overnight, and calcining at 700°C for 4h to obtain the zinc-aluminum spinel oxide;

[0026] Sodium-promoted zinc aluminum spinel supported iron-based catalyst: 0.59 g of zinc aluminum spinel oxide, 0.81 g of Fe(NO3)3·9H2O and 0.04 g of NaNO3 were mixed, uniformly mixed by physical mixing, and then calcined at 550°C for 4 hours.

[0027] The catalyst was loaded into the reaction tube and subjected to carbon dioxide hydrogenation reaction on the high-pressure catalytic evaluation system. The hydrogen reduction was pretreated for 18 hours, and then a mixture of H2 and CO2 with a volume ratio of 3:1 was introduced. The hydrogenation to olefins was carried out under the conditions of reaction temperature of 280°C, pressure of 2.5MPa, and space velocity of 1800ml / (g*h). The reaction time was 75 hours. The catalytic performance is shown in Table 1.

[0028] Example 2

[0029] The catalyst preparation is the same as that in Example 1; the difference in application is that the carbon dioxide hydrogenation reaction conditions are temperature 300°C, pressure 2.5MPa, and space velocity 1800ml / (g*h). The catalytic performance is shown in Table 1.

[0030] Example 3

[0031] The catalyst preparation is the same as that in Example 1, and the difference in application is that the carbon dioxide hydrogenation reaction conditions are temperature 320°C, pressure 2.5MPa, and space velocity 1800ml / (g*h). The catalytic performance is shown in Table 1.

[0032] Example 4

[0033] The catalyst preparation is the same as in Example 1, and the difference in application is that the carbon dioxide hydrogenation reaction conditions are temperature 340°C, pressure 2.5MPa, and space velocity 1800ml / (g*h). The catalytic performance is shown in Table 1.

[0034] Example 5

[0035] The catalyst preparation is the same as in Example 1, and the difference in application is that the carbon dioxide hydrogenation reaction conditions are temperature 360°C, pressure 2.5MPa, and space velocity 1800ml / (g*h). The catalytic performance is shown in Table 1.

[0036] Example 6

[0037] The catalyst preparation is the same as that in Example 1, and the difference in application is that the carbon dioxide hydrogenation reaction conditions are temperature 380°C, pressure 2.5MPa, and space velocity 1800ml / (g*h). The catalytic performance is shown in Table 1.

[0038] From the catalytic results of Examples 1-6, it can be seen that the higher the reaction temperature, the higher the CO2 conversion rate, the lower the CO selectivity, but the CH4 selectivity also increases; when the reaction temperature increases from 280°C to 300°C, C2= -C4 = The selectivity increases as the reaction temperature further increases. = -C4 = The selectivity begins to decrease. When the reaction temperature rises from 280℃ to 320℃, O / P increases, but as the reaction temperature further increases, O / P also begins to decrease. In general, although the reaction temperature is above 300℃, C2 = -C4 = The selectivity begins to decrease, but the STY value is the highest at 360°C among these reaction temperatures, so it can be determined that 360°C is the optimal reaction temperature. Next, the reaction temperature remains unchanged at 360°C, and different space velocities are changed to study the optimal reaction space velocity.

[0039] Example 7

[0040] The catalyst preparation is the same as that in Example 1, except that the reaction conditions for the carbon dioxide hydrogenation are a temperature of 360°C, a pressure of 2.5 MPa, and a space velocity of 1400 ml / (g*h). The catalytic performance is shown in Table 1.

[0041] Example 8

[0042] The catalyst preparation is the same as that in Example 1, except that the reaction conditions for the carbon dioxide hydrogenation are a temperature of 360°C, a pressure of 2.5 MPa, and a space velocity of 2200 ml / (g*h). The catalytic performance is shown in Table 1.

[0043] Example 9

[0044] The catalyst preparation is the same as that in Example 1, except that the reaction conditions for the carbon dioxide hydrogenation are a temperature of 360°C, a pressure of 2.5 MPa, and a space velocity of 2600 ml / (g*h). The catalytic performance is shown in Table 1.

[0045] Example 10

[0046] The catalyst preparation is the same as that in Example 1, except that the carbon dioxide hydrogenation reaction conditions are temperature 360°C, pressure 2.5 MPa, and space velocity 3000 ml / (g*h). The catalytic performance is shown in Table 1.

[0047] From the catalytic results of Examples 7-10, it can be seen that as the space velocity increases, the CO2 conversion rate decreases, the CO selectivity increases, and the methane is essentially unchanged; when the reaction space velocity increases from 1400ml / (g*h) to 1800ml / (g*h), C2 = -C4 = Selectivity increases, as the airspeed increases further, C2 = -C4 =The selectivity decreased slightly. When the reaction space velocity increased from 1400ml / (g*h) to 2200ml / (g*h), the O / P ratio increased, but as the space velocity increased further, the O / P ratio showed a downward trend, but it was not obvious. Overall, although the reaction space velocity was 1800ml / (g*h) after C2 = -C4 = The selectivity begins to decrease, but the STY is the highest at a reaction space velocity of 2600 ml / (g*h), so 2600 ml / (g*h) can be determined as the optimal reaction space velocity. Combined with the catalytic results of Examples 1-6, the optimal reaction conditions are a temperature of 360°C, a pressure of 2.5 MPa, and a space velocity of 2600 ml / (g*h).

[0048] Comparative Example 1

[0049] The catalyst preparation is different from that in Example 1 except that the carrier calcination temperature is changed to 800°C. The rest is the same as in Example 1.

[0050] The carbon dioxide hydrogenation reaction was the same as in Example 9, that is, the reaction conditions were a temperature of 360°C, a pressure of 2.5 MPa, and a space velocity of 2600 ml / (g*h). The catalytic performance is shown in Table 1.

[0051] Comparative Example 2

[0052] The catalyst preparation is different from that in Example 1, except that the carrier calcination temperature is changed to 900° C. The carbon dioxide hydrogenation reaction is the same as in Example 9. The catalytic performance is shown in Table 1.

[0053] Comparative Example 3

[0054] The catalyst preparation is different from that in Example 1, except that the carrier calcination temperature is changed to 600° C. The carbon dioxide hydrogenation reaction is the same as in Example 9, and the catalytic performance is shown in Table 1.

[0055] Comparative Example 4

[0056] The catalyst preparation method is different from that in Example 1.

[0057] Zinc aluminum spinel: 1.49 g Zn(NO3)2·6H2O and 3.75 g Al(NO3)3·9H2O were uniformly mixed by a mechanical synthesis method, and the obtained mixture was calcined at 700° C. for 4 h to obtain the zinc aluminum spinel oxide;

[0058] Sodium-promoted zinc-aluminum spinel supported iron-based catalyst: 0.59 g of zinc-aluminum spinel oxide, 0.81 g of Fe(NO3)3·9H2O and 0.04 g of NaNO3 were mixed and uniformly mixed by physical mixing, and then calcined at 550°C for 4 hours. The carbon dioxide hydrogenation reaction conditions were temperature 360°C, pressure 2.5 MPa, and space velocity 2600 ml / (g*h). The catalytic performance is shown in Table 1.

[0059] Under the same reaction conditions: temperature 360°C, pressure 2.5MPa, space velocity 2600ml / (g*h), the carbon dioxide hydrogenation reaction was carried out for 75h. Compared with comparative examples 1-4, Example 9 showed the highest olefin selectivity and STY. It is worth noting that the CO2 conversion rate of all samples in the present invention is above 20%, which is higher than the CO2 conversion rate of all samples in Chinese patent CN110496639A.

[0060] Table 1 Catalytic performance of Examples 1-10 and Comparative Examples 1-4

[0061]

[0062] The catalysts of all examples were subjected to X-ray powder diffraction (XRD) experiments, and the results are as follows: Figure 1 and 2 shown.

[0063] The catalysts of Example 9 and Comparative Examples 1-4 were subjected to stability tests under the carbon dioxide hydrogenation reaction conditions of Example 9. The results are as follows: Figure 3 As shown, through experimental verification, it shows a good catalytic effect and good thermal stability. It still maintains good catalytic activity after a long time (75h), and has great potential applications in the field of carbon dioxide hydrogenation.

Claims

1. A method for preparing a sodium-promoted zinc-aluminum spinel-supported iron-based catalyst, characterized in that: (1) preparing a mixed metal salt aqueous solution with a zinc salt and an aluminum salt; contacting the mixed metal salt aqueous solution with a precipitant aqueous solution until a fixed pH value of 10 is reached, so that metal ions in the mixed metal salt aqueous solution are co-precipitated; Heating and stirring until complete precipitation; washing, drying and calcining the precipitate to obtain a zinc-aluminum spinel oxide carrier; the molar ratio of zinc salt to aluminum salt is 1:2; (2) Iron salt, sodium salt and zinc aluminum spinel oxide carrier are mixed by physical mixing method, calcined, and sodium-promoted zinc aluminum spinel supported iron-based catalyst is obtained; the mass ratio of surface iron salt to carrier is 1:1-1.5; the molar ratio of iron salt to sodium salt is 7:1.5-1.

8.

2. The method for preparing the sodium-promoted zinc-aluminum spinel-supported iron-based catalyst according to claim 1, characterized in that: The zinc salt is selected from one or more of zinc acetate, zinc sulfate and zinc nitrate; the aluminum salt is selected from one or more of aluminum acetate, aluminum sulfate, aluminum nitrate and aluminum isopropoxide; the precipitant is selected from one or more of sodium carbonate, potassium carbonate, ammonium carbonate, sodium bicarbonate, potassium bicarbonate, ammonium bicarbonate, ammonia water, sodium hydroxide and potassium hydroxide.

3. The method for preparing the sodium-promoted zinc-aluminum spinel-supported iron-based catalyst according to claim 1, characterized in that: The coprecipitation is carried out at 40°C to 80°C.

4. The method for preparing the sodium-promoted zinc-aluminum spinel-supported iron-based catalyst according to claim 1, characterized in that: The calcination temperature in step (1) is 600°C to 900°C.

5. The method for preparing the sodium-promoted zinc-aluminum spinel-supported iron-based catalyst according to claim 1, characterized in that: The calcination temperature in step (2) is 550°C to 600°C.

6. A method for preparing olefins by hydrogenating carbon dioxide, characterized in that: The sodium-promoted zinc-aluminum spinel-supported iron-based catalyst prepared by the method described in any one of claims 1 to 5 is loaded into a catalytic reactor, first pre-treated with hydrogen reduction, and then switched to a mixed gas of H2 and CO2 in a volume ratio of 2:1 to 4:1, and hydrogenated to produce olefins under the conditions of a reaction temperature of 280 to 380°C, a pressure of 2.4 to 2.6 MPa, and an air velocity of 1400 to 3000 ml / (g*h).

7. The method for preparing olefins by hydrogenating carbon dioxide according to claim 1, characterized in that: The reaction temperature is 360°C, the reaction pressure is 2.5 MPa, and the space velocity is 2600 ml / (g*h).

Citation Information

Patent Citations

  • Catalyst for synthesizing aromatic hydrocarbon and preparation method and application of catalyst

    CN110496639A

  • Method for preparing low-carbon olefins from synthesis gas by direct catalytic conversion

    CN109999816A

  • Catalyst for preparing low-carbon olefin through carbon monoxide hydrogenation and application thereof

    CN112705258A

  • Modified zinc aluminate carrier, low-carbon alkane dehydrogenation catalyst as well as preparation method and application of modified zinc aluminate carrier and low-carbon alkane dehydrogenation catalyst

    CN114950401A

  • Fe-based alloy carbide, preparation method of Fe-based alloy carbide and application of Fe-based alloy carbide in preparation of ethanol and co-production of olefin through hydrogenation of carbon dioxide

    CN117414853A